Enhanced Tensile Properties and Fracture Reliability of Cu‐Based Amorphous Wires via Pr‐Doping. Issue 6 (12th February 2018) - Liu, Jingshun; Zhang, Yun; Wang, Qixiang; Wu, Mengjun; Nan, Ding; Shen, Hongxian; Peng, Huaxin
Abstract : This paper proposed a novel wire‐preparation technique integrated Pr‐doping to improve the tensile properties of rotation‐dipped Cu‐based amorphous wires, and systematically investigates the fracture reliability and fracture mechanism of them. Meanwhile, the mechanical properties are evaluated through tensile tests, and their fracture reliability is estimated by using two‐ and three‐parameter Weibull statistics and lognormal plotting. Experimental results indicate that the Cu‐based wires have entirely amorphous microstructure, a smooth surface and circular cross‐section, and exhibit a relatively higher working temperature. Both the Cu–Zr–Ti and Cu–Zr–Ti–Pr wires represent the higher tensile strengths. In comparison with Cu–Zr–Ti wires, Cu–Zr–Ti–Pr wires possess a maximum tensile strength and ductility of 2.07 GPa and 0.92%, respectively. Meanwhile, Cu–Zr–Ti–Pr wires also exhibit a larger Weibull modulus, which stand for the fracture reliability in Weibull statistics, and higher fracture threshold stress (≈1.42 GPa). Essentially, both fracture of two types of Cu‐based wires take on a brittle fracture characteristic with crack extension region and shear deformation region, and the improved tensile property after Pr‐doping is probably attributed to the strengthened interaction of shear bands and micropore gathering (vein‐shaped pattern forming). Therefore, it can be concluded that the Cu‐based microwires with enhanced tensile property as the ideal candidates including miniaturized components are used for potential electronics engineering and biomedical implantation applications. Abstract : Tensile properties of Cu‐based microwires are effectively enhanced by using Pr‐doping in comparison with strain–stress curves. Fracture morphology of both side view and front view shows typical fracture regions. Moreover, tensile deformation process of Cu‐based wires includes four stages: elastic deformation, free volume gathered and rheological defect fusion, growth of shear band and the formation of vein‐shaped pattern, and fracture.